Room temperature processed in-situ carbon-coated vanadium carbide (VC@C) as a high capacity robust Li/Na battery anode material - Mahajan, Mani; Roy, Kingshuk; Parmar, Swati; Singla, Gourav; Pandey, O. P.; Singh, K.; Vaidhyanathan, Ramanathan; Ogale, Satishchandra (Carbon, 2020)
3D carbide systems with their robust physical and mechanical properties have always attracted multiple application interests. In this report, we have synthesized a three-dimensional in-situ carbon coated cubic carbide, Vanadium Carbide (VC@C), by a very simple, scalable and cost-effective room temperature mechano-chemical ball-milling procedure and researched its promise as effective anode material for Li and Na ion batteries. We have demonstrated that VC@C shows an impressive initial discharge/lithiation capacity of 1165 mAh g(-1) with a high reversible capacity of 640 mAh g(-1) after 100 charge-discharge cycles at an applied current density of 0.1 A g(-1). We have also found that this material renders a very promising rate performance with significantly low capacity drop after exposing it to variable current densities ranging from 0.05 A g(-1) to 2 A g(-1) with an excellent stability up to 1000 cycles owing to its structural robustness, as verified by post-cycling characterizations. A Li-ion full cell study using LiCoO2 as cathode also showed excellent promise in terms of practical application demonstrating a reversible capacity of 95 mAh g(-1) after 100 cycles. Even for Na insertion/de-insertion VC@C shows a clear promise in terms of capacity, cyclic stability and rate performance. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 3D carbide; In-situ synthesis; Li-ion battery; Post cycling characterization; Room temperature ball milling; Williamson-Hall analysis

Facile synthesis of CNT interconnected PVP-ZIF-8 derived hierarchically porous Zn/N co-doped carbon frameworks for oxygen reduction dagger - Singla, Gourav; Bhange, Siddheshwar N.; Mahajan, Mani; Kurungot, Sreekumar (Nanoscale, 2021)
In this work, a strategy has been adopted to construct an architecture through the coordination of polyvinylpyrrolidone (PVP) and a monodisperse zeolitic imidazolate framework (ZIF-8), which was entwined by carbon nanotubes (CNTs) firstly, followed by a pyrolysis process to obtain the hybrid catalyst. The meticulous design of the hybrid material using CNTs to interconnect the PVP assisted ZIF-8 derived porous carbon frameworks together produces a hierarchical pore structure and dual-heteroatom (Zn/N) doping (Zn-N/PC@CNT). Without further acid treatment, the hybrid material prepared after pyrolysis at 900 degrees C (PVP-ZIF-8@CNT-900) has been demonstrated as an efficient non-precious metal catalyst for the oxygen reduction reaction (ORR) with its superior stability compared to the commercial 20 wt% Pt/C catalyst in alkaline media. The catalyst shows better performance towards the ORR, with its more positive onset and half-wave potentials (E-onset = 0.960 V vs. RHE and E-1/2 = 0.795 V vs. RHE) than the counterpart system which is free of both CNT and PVP. The high performance of the hybrid catalyst can be ascribed to the co-existence of dual-active sites with hierarchical pore structures originating from the synergistic effects between Zn/N co-doped porous carbon and CNTs. We further demonstrated the single-cell performance by using the homemade system as the cathode catalyst for the Alkaline Exchange Membrane Fuel Cell (AEMFC) system, which showed a maximum power density of 45 mW cm(-2) compared to 60 mW cm(-2) obtained from the 40 wt% Pt/C catalyst.

Fabrication of a 3D iron-modified NiCo2S4 structure on nickel foam as a bifunctional electrocatalyst for overall water splitting - Singla, Gourav; Mahajan, Mani; Bhange, Siddheshwar N.; Kashyap, Varchaswal (New Journal of Chemistry, 2025)
The development of highly efficient bifunctional electrocatalysts that operate effectively in strong electrolytes, with low overpotentials at defined current densities and excellent durability, has become a central focus in research on overall water splitting. In this study, a three-dimensional (3D) sheet-wrapped wire electrocatalyst, composed of Fe-doped NiCo2S4 on nickel foam (NF), was fabricated. This material demonstrated excellent durability for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an alkaline medium. The uniform distribution of Ni, Co, Fe, and S elements significantly enhanced the electro-catalytic performance. The incorporation of Fe improved activity, with the Fe2.5%-NiCo2S4/NF electrocatalyst achieving overpotentials of 310 mV and 260 mV for the HER and OER, respectively, at a current density of 100 mA cm-2. These results were superior to those of both bare nickel foam and NiCo2S4/NF. The 3D configuration facilitated efficient ion transport and contributed to the remarkable catalytic performance. As a water-splitting electrolyzer in an alkaline electrolyte of 1.0 M KOH, the system delivered a current density of 20 mA cm-2 at a cell voltage of 1.66 V, highlighting the effectiveness of this design strategy.